THE METHOD OF SAFE MULTIPATH ROUTING IN MPLS WIRELESS - Кулаков, Ю.; Лукашенко, В.; Левчук, А. (Proceedings of National Aviation University (archive), 2012)
The paper proposes a way to organize a safe Multipath routing in wireless MPLS, which will greatlyimprove the speed of information processing and protect datatraffic.